2002
DOI: 10.1152/jn.2002.88.3.1393
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of Sensory Neurons to Tumor Necrosis Factor α in Rats With Chronic Compression of the Lumbar Ganglia

Abstract: Proinflammatory cytokines may sensitize primary sensory neurons and facilitate development of neuropathic pain processes after peripheral nerve injury. The goal of this study was to determine whether responses of dorsal root ganglion (DRG) neurons to exogenous tumor necrosis factor alpha (TNF-alpha) are altered in a chronically compressed DRG (CCD) injury model. Extracellular recordings from teased dorsal root microfilaments demonstrated that acute topical application of TNF-alpha to the DRG for 15 min evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 31 publications
5
49
0
2
Order By: Relevance
“…The observed lack of calciumpermeable AMPA/KA receptor involvement in maintenance of secondary mechanical allodynia may be due to a decrease in membrane receptor density caused by clathrin-mediated endocytosis (Lin et al, 2000). Previous electrophysiological studies demonstrate that calcium-permeable AMPA receptors rapidly internalize after their activation (Liu and Cull-Candy, 2000;Liu et al, 2002). Receptor, or receptor subunit, cycling in and out of the postsynaptic membrane (Lissin et al, 1999) may very well shift the level of calcium-permeable AMPA receptor involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The observed lack of calciumpermeable AMPA/KA receptor involvement in maintenance of secondary mechanical allodynia may be due to a decrease in membrane receptor density caused by clathrin-mediated endocytosis (Lin et al, 2000). Previous electrophysiological studies demonstrate that calcium-permeable AMPA receptors rapidly internalize after their activation (Liu and Cull-Candy, 2000;Liu et al, 2002). Receptor, or receptor subunit, cycling in and out of the postsynaptic membrane (Lissin et al, 1999) may very well shift the level of calcium-permeable AMPA receptor involvement.…”
Section: Discussionmentioning
confidence: 99%
“…؉ currents Previous studies have reported that TNF␣ can evoke action potentials and increase discharge rates when applied locally to nociceptive neurons (Sorkin et al, 1997;Junger and Sorkin, 2000;Sorkin and Doom, 2000;Liu et al, 2002). The mechanisms underlying this alteration in firing are not known, and we hypothesized that this effect of TNF␣ might be mediated in part by modulation of TTX-R Na ϩ channels.…”
Section: Tnf␣ Enhances Ttx-r Namentioning
confidence: 96%
“…In chronic constriction injury (CCI), an animal model of injury-induced painful mononeuropathy, inhibition of TNF␣ synthesis and release results in reduced pain behavior (Lindenlaub et al, 2000). In rat dorsal root ganglion (DRG), acute topical application of TNF␣ increases the firing rate of sensory neurons in normal rats and rats subjected to chronic DRG compression (Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%